Stage-specific function of sphingolipid synthases in African trypanosomes - Norton Heise; Carolina M. Koeller; Mohamed Sharif; James D. Bangs (mBio)
ABSTRACT The protozoan parasite Trypanosoma brucei is the only known eukaryote capable of synthesizing the three main phosphosphingolipids: sphingomyelin (SM), inositol phosphorylceramide (IPC), and ethanolamine phosphorylceramide (EPC). It has four paralogous genes encoding sphingolipid synthases (TbSLS1–4). TbSLS1 is a dedicated IPC synthase, TbSLS2 is a dedicated EPC synthase, and TbSLS3 and TbSLS4 are bifunctional SM/EPC synthases. IPC synthesis occurs exclusively in the procyclic insect stage (PCF), EPC is limited to the mammalian bloodstream form (BSF), and SM is synthesized throughout the life cycle. TbSLSs are indispensable for the viability of BSF and are, thus, potential drug targets. The relative stage-specific expression of each TbSLS paralog was compared, and the results match phosphosphingolipid content. Induction of pan-specific RNAi silencing was lethal in both BSF and PCF. To investigate individual TbSLS functions, separate HA-tagged genes, recoded to be RNAi-resistant (RNAiR), were engineered to replace a single allele of the entire TbSLS locus within parental BSF and PCF RNAi cell lines. RNAiR TbSLS3 and TbSLS4 both rescued BSF growth under silencing. Expression of RNAiR TbSLS1, normally repressed in BSF, did not rescue BSF viability but was not detrimental to normal in vitro growth. RNAiR TbSLS1, TbSLS3, and TbSLS4 were each sufficient to rescue PCF growth, indicating IPC is not essential for PCF viability in vitro. All TbSLSs localize to distal Golgi compartments in both BSF and PCF cells. These findings raise interesting questions about the roles of individual phosphosphingolipids in in vivo infection of the mammalian and tsetse hosts.IMPORTANCEAfrican trypanosomes are eukaryotic pathogens that cause human and veterinary African trypanosomaisis. Uniquely, they synthesize all three major phosphosphingolipid species using four distinct sphingolipid synthases (SLS). This work details the function of each SLS in both bloodstream and insect form parasites. Novel and unexpected sphingolipid dependences are found in each stage. These results are consistent with this metabolic pathway being a valid target for chemotherapeutic intervention.